Analysis of the Legality of the Enactment of Law Number 2 of 2012 in the Implementation of Land Acquisition for Development for Public Interest, from a Review of Fulfillment of Legal Basic Values - Ismiyanto, Ismiyanto; Sudarwanto, AL Sentot; Handayani, I Gusti Ayu Ketut Rachmi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This study aims to conduct a study and analysis of the substance of Law Number 2 of 2012 concerning Land Acquisition for Development for Public Interest, in order to ascertain whether the law has met the basic values of the law, so that it can be seen to what extent its validity is valid from philosophical, juridical, and sociological reviews. This research is a normative or doctrinal legal research, using a statute approach, while the type of data is secondary, obtained from document review and literature study of primary, secondary and tertiary legal materials. The analysis technique uses an interactive model. The results of this study indicate that the land acquisition legal system or Law Number 2 of 2012 has validity from a juridical review, but does not have validity from a philosophical review and from a sociological review. Based on the results of the above research, it is recommended that the Government immediately revise Law Number 2 of 2012. Key words: validity, land acquisition, fair